Evaluation of herringbone carbon nanotubes-modified electrodes for the simultaneous determination of ascorbic acid and uric acid. (20th September 2018) - Abellán-Llobregat, A.; Vidal, L.; Rodríguez-Amaro, R.; Canals, A.; Morallón, E.
Abstract: An array of gold interdigitated microelectrodes (Au-IDA) has been modified by casting herringbone carbon nanotubes (hCNTs) producing a new electrochemical sensor suitable for the simultaneous determination of ascorbic acid (AA) and uric acid (UA) in PBS (0.25 M, pH 7.0). The sensor showed good electrocatalytic properties for both analytes with low working potentials, linear ranges between 0 and 600 μM for AA, and between 0 and 420 μM for UA. The empirical limits of detection (LODs) and the limits of quantification (LOQs) for both analytes were 15 μM and 50 μM, respectively. Moreover, UA does not interfere in the measurement of AA and vice versa. Furthermore, the presence of common analytes in physiological fluids as glucose, dopamine and epinephrine do not interfere in the quantification neither AA nor UA.